2007
DOI: 10.2190/de.37.4.e
|View full text |Cite
|
Sign up to set email alerts
|

Alprazolam (Xanax®) Use among Southern Youth: Beliefs and Social Norms concerning Dangerous Rides on “Handlebars”

Abstract: While the epidemiologic trends concerning alprazolam (Xanax) are unknown, the use of benzodiazepines, in general, has increased in popularity among youth within recent years. To shed light on the drug problem, the current pilot study used a qualitative approach to investigate relevant beliefs, norms, and perceived addiction associated with alprazolam initiation among 46 youth who were attending an inpatient drug treatment program during the spring of 2004. Overwhelmingly, most participants stated that addictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Some researchers suggest continuing use of alprazolam (Australian Bureau of Statistics, 2010; SDI/ Verispan, 2010) may represent ongoing clinical management of chronic conditions rather than drug dependence (Romach et al, 1991(Romach et al, , 1992Sellers et al, 1993). A qualitative investigation of youth attitudes concerning alprazolam revealed use was deemed common, the drug was highly addictive, difficult to cease and medical professionals were the greatest facilitators of use (Peters et al, 2007), indicating that at least a portion of ongoing use may relate to drug dependence.…”
Section: Wider Issues With Alprazolam Abuse Potential and Non-clinical Effectsmentioning
confidence: 99%
“…Some researchers suggest continuing use of alprazolam (Australian Bureau of Statistics, 2010; SDI/ Verispan, 2010) may represent ongoing clinical management of chronic conditions rather than drug dependence (Romach et al, 1991(Romach et al, , 1992Sellers et al, 1993). A qualitative investigation of youth attitudes concerning alprazolam revealed use was deemed common, the drug was highly addictive, difficult to cease and medical professionals were the greatest facilitators of use (Peters et al, 2007), indicating that at least a portion of ongoing use may relate to drug dependence.…”
Section: Wider Issues With Alprazolam Abuse Potential and Non-clinical Effectsmentioning
confidence: 99%
“…In the peer domain, Collins and colleagues found that friends’ use was a significant predictor of prevalence of marijuana, inhalants, and other drugs (including narcotics and uppers) (Collins, Pan, Johnson, Courser, & Shamblen, 2008). And, Peters, Meshack, and Kelder (2007) reported that peer reinforcement was a main reason given by youth for using Xanax (Alprazolam) non-medically the first time.…”
Section: Introductionmentioning
confidence: 99%
“…Use has been found to increase with age [22]. Individual risk factors such as deviant [24] and sensation-seeking behaviors [25], and peer influence [26] are two of the main reasons why youth initiate the use of prescription drugs non-medically. Other risk factors include previous medical use of prescription drugs [22], availability [27], and urbanicity [28].…”
Section: Introductionmentioning
confidence: 99%